Application of Microsatellite Markers for Genetic Diversity Analysis of Indonesian Local Cattle - Dwi Hariyono (WARTAZOA. Indonesian Bulletin of Animal and Veterinary Sciences, 2022)
Animal genetic resources (AnGR), including cattle, have been valuable national assets that need to be preserved and developed. There are at least 16 recognized breeds of cattle that have been registered as local and new breeds by the Ministry of Agriculture of the Republic of Indonesia. Conservation and development programs of these local cattle breeds require basic information regarding their genetic diversity, relationships, and structures. There are several types of DNA markers that can be used for genetic diversity analysis, such as microsatellite markers. Microsatellites or short tandem repeats (STRs) are a group of DNA sequences consisting of tandemly repeated units (1–6 bp), which are abundant throughout the genome and can be found in both coding and non-coding regions. The primary advantages of microsatellites are that they are inherited in a Mendelian pattern (codominant markers), high polymorphism rates, and high abundances throughout the genome. The aim of this review is to discuss the application of microsatellite markers for genetic diversity analysis in Indonesian local cattle based on 3 indices: number alleles per locus, expected heterozygosity (He), and polymorphisms information content (PIC). There are at least 28 microsatellite markers that have been studied in Indonesian local cattle, with the number of alleles per locus ranging from 2 to 32, He values ranging from 0.100 to 0.985, and PIC values from 0.095 to 0.935. Based on the PIC values, several microsatellites are classified as highly informative, e.g. BM1824, ILST6, TGLA126, TGLA53, TGLA227, TGLA122, ETH225, INRA23, SPS113, SPS115, BM1818, CSSM66, ETH10, INRA005, INRA037, ETH185, HEL017, and ILSTS029. Therefore, these microsatellite markers can be potentially used for future genetic diversity analysis of other breeds of cattle.